2015
DOI: 10.1093/mnras/stv519
|View full text |Cite
|
Sign up to set email alerts
|

A high-sensitivity polarimeter using a ferro-electric liquid crystal modulator

Abstract: We describe the HIgh Precision Polarimetric Instrument (HIPPI), a polarimeter built at UNSW Australia and used on the Anglo-Australian Telescope (AAT). HIPPI is an aperture polarimeter using a ferro-electric liquid crystal modulator. HIPPI measures the linear polarization of starlight with a sensitivity in fractional polarization of ∼4 × 10 −6 on low polarization objects and a precision of better than 0.01% on highly polarized stars. The detectors have a high dynamic range allowing observations of the brightes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
108
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(111 citation statements)
references
References 28 publications
(49 reference statements)
1
108
0
Order By: Relevance
“…Between September 2016 and April 2019 we also made 29 new high-precision polarimetric observations of α Oph in seven photometric bands with a variety of instrument and telescope configurations. The bulk of the observations were made using HIPPI (HIgh Precision Polarimetric Instrument, Bailey et al 2015) and its successor HIPPI-2 (Bailey et al 2020) at the 3.9-m Anglo-Australian Telescope (AAT) at Siding Spring Observatory. Two observations were made at the Gemini North telescope on Mauna Kea with HIPPI-2.…”
Section: Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Between September 2016 and April 2019 we also made 29 new high-precision polarimetric observations of α Oph in seven photometric bands with a variety of instrument and telescope configurations. The bulk of the observations were made using HIPPI (HIgh Precision Polarimetric Instrument, Bailey et al 2015) and its successor HIPPI-2 (Bailey et al 2020) at the 3.9-m Anglo-Australian Telescope (AAT) at Siding Spring Observatory. Two observations were made at the Gemini North telescope on Mauna Kea with HIPPI-2.…”
Section: Observationsmentioning
confidence: 99%
“…However, subsequent studies using more complete stellar-atmosphere models showed that the expected polarization was small at visible wavelengths (Collins 1970;Sonneborn 1982). It was not until the development of polarimeters that could measure linear polarization to parts-per-million (ppm) levels of precision (Hough et al E-mail: j.bailey@unsw.edu.au 2006; Bailey et al 2015) that the effect was detected (Bailey et al 2010) and confirmed by multiwavelength polarimetry and detailed modelling of the bright star Regulus (α Leo; Cotton et al 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…The 20th century data sets used in this analysis included the discovery of the ISMF within 40 pc of the Sun in the fourth galactic quadrant (ℓ = 270°-360°, Piirola 1977;Tinbergen 1982). More recently, high sensitivity polarimeters capable of 3σ detections of polarization strengths <0.01% have become available (Pereyra & Magalhães 2007;Wisniewski et al 2007;Bailey et al 2010Bailey et al , 2015Berdyugin et al 2014;Piirola et al 2014;.…”
Section: Polarization Data Used To Determine the Magnetic Field Direcmentioning
confidence: 99%
“…Moreover, the "instant" readout allows one to use PMT with the fast polarization modulator such as PEM or FLC. Not surprisingly, the PMT detectors have been used in the most precise polarimeters such as HIPPI (Bailey et al, 2015) and POLISH2 (Wiktorowicz and Nofi, 2015). The major disadvantage of the PMT detectors is their relatively low quantum efficiency which is typically in the range 10-30%.…”
Section: Detectors For Optical Polarimetry: Photomultiplier Tubesmentioning
confidence: 99%
“…HIPPI, a successor to PlanetPol (Bailey et al, 2015), employs the FLC modulator, operated at the frequency of 500 Hz, and PMT detectors. Unlike PlanetPol, it is optimized for high-precision polarimetry in the blue wavelengths, in the spectral region ∼ 400-700 nm.…”
Section: High-precision Double-image Polarimeters With High-frequencymentioning
confidence: 99%